Data‐Driven Residency Training: A Scoping Review of Educational Interventions for Neurosurgery Residency Programs. Issue 5 (November 2021) - Kelly, Patrick D; Yengo‐Kahn, Aaron M; Roth, Steven G; Zuckerman, Scott L; Chitale, Rohan V; Wellons, John C; Chambless, Lola B
Abstract : BACKGROUND: : Neurosurgery residency programs are tasked with imparting large volumes of both clinical knowledge and technical skill to trainees in limited time. Many investigators have described local practices, which may offer evidence‐based interventions in neurosurgical residency education, but this literature has not been systematically reviewed. OBJECTIVE: : To perform a scoping review of educational practices in neurosurgery, which are supported by quantitative, peer‐reviewed research. METHODS: : A scoping review of the literature was performed. PubMed, Embase, and Web of Science databases were queried for articles describing educational interventions for neurosurgery residents, which included a quantitative assessment of the effect on resident performance. RESULTS: : From an initial set of 1785 unique articles, 29 studies were ultimately screened and included. Studies were into the following 6 topics: (1) didactics and curricula (n = 13), (2) nontechnical skills (n = 6), (3) wellness and burnout (n = 4), (4) assessment and feedback (n = 2), (5) mentorship and career development (n = 2), and (6) research (n = 2). Individual study results were described. CONCLUSION: : Several educational interventions in neurosurgical training are supported by quantitative evidence. Methodological shortcomings are prevalent among studies of education, particularly in the selection of meaningful outcome measures. A summary of evidence‐based considerations is provided for current and future program directors.